Tajikistan - Lerner Publications Company. Geography Dept. (Minneapolis : Lerner Publications Co., 1993)
Discusses the geography, history, people, economics, politics, and future of the central Asian country that was the smallest and poorest Soviet republic.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
6.9
4-6
Keywords: Tajikistan -- Juvenile literature; Tajikistan; Tajikistan